(untitled) (Journal of Nepal Geological Society, 2000)
The hilly region of Western Ghats, India, is a site of frequent landslides, which have caused a severe loss of lives and property. The region is characterised by the presence of residual soils, rugged topography, high relief, and medium to steep slopes. During the heavy rainfall, the pore water pressure is built quickly in the residual soils. This study deals with a probabilistic stability analysis of rain-induced failures on residual soil slopes. A mass movement analysis is also attempted using the momentum transfer law for the Parmachi Landslide. Attention is given to the associated risk of sliding, incorporating important factors, which influence the failure of natural slopes. A landslide hazard prediction procedure is presented and its application to debris flows at Parmachi is shown as an example. The probability of failure is evaluated in conjunction with the consequences of failure. Decision analysis is also tried with the probabilistic slope stability analysis of the Parmachi Landslide. The evaluated risk and decision theory are used to suggest a decision-making process for landslide hazard mitigation.